The Strange Fate Of A Foreign Tort In A Malaysian Court: Chan Kwon Fong & Anor v Chan Wah - Hickling, R.H. (Journal of Malaysian and Comparative Law, 2018)
Case Note The Strange Fate Of A Foreign Tort In A Malaysian Court: Chan Kwon Fong & Anor v Chan Wah